STUDENTS' BEHAVIORAL ENGAGEMENT THROUGH KWL STRATEGY IN READING COMPREHENSION - Dhenda Rizki Gunawan; Maya Rahmawati (British : Jurnal Bahasa dan Sastra Inggris, 2022)
This study aims to determine the extent of the involvement of students' behavior with the KWL strategy in reading comprehension. To find out students' responses to students' reading comprehension using the KWL strategy. The research method used is descriptive with a qualitative approach. The sample used in this study was only 28 students who were taken from one class. The sample used in this study was only 28 students who were taken from one clas. The data analysis used consisted of collecting data, examining and reviewing data until the last process, namely the presentation of data in narrative form. The students gave positive feedback. First, the KWL strategy can help students in reading comprehension. The KWL strategy really helps students understand by reading English faster, making students have a great learning experience in reading. Second, the KWL strategy makes students active in analyzing reading comprehension. Students are able to understand and analyze reading well and correctly, students study it carefully using the KWL strategy to get reading comprehension through report text. Finally, the KWL strategy can offer learning that makes students more enthusiastic in learning reading comprehension, almost all students feel enthusiastic about reading comprehension through the KWL strategy.